Correction to: Effects of Long-term Climate Change on Typhoon Rainfall Associated with Southwesterly Monsoon Flow near Taiwan: Mindulle (2004) and Morakot (2009) - Chung-Chieh Wang; Li-Shan Tseng; Chien-Chang Huang; Pi-Yu Chuang; Nan-Chou Su; Cheng-Ta Chen; Shih-How Lo; Kazuhisa Tsuboki (Asia-Pacific Journal of Atmospheric Sciences, 2024)

Effects of Long-term Climate Change on Typhoon Rainfall Associated with Southwesterly Monsoon Flow near Taiwan: Mindulle (2004) and Morakot (2009) - Chung-Chieh Wang; Li-Shan Tseng; Chien-Chang Huang; Pi-Yu Chuang; Nan-Chou Su; Cheng-Ta Chen; Shih-How Lo; Kazuhisa Tsuboki (Asia-Pacific Journal of Atmospheric Sciences, 2024)

Impact of Pacific–Japan pattern on temperature and heatwave events in summer over Taiwan - Wan‐Ling Tseng; Szu‐Ying Lin; Yi‐Chi Wang; Shih‐How Lo; Min‐Hui Lo; Shih‐Yu Lee; Chieh‐Ting Tsai; Huang‐Hsiung Hsu (International Journal of Climatology, 2023)
The prediction of heatwave events is vital to provide information on possible hazards caused by extremely high temperature. The Pacific–Japan (PJ) pattern is a significant climate variability that controls the summer climate over East Asia. Previous studies have reported that the meridional propagating wave structure associated with the PJ pattern can modulate summer temperature and heatwave characteristics over northeast Asian countries, such as Korea and Japan. Nevertheless, its impacts on the subtropical regions, including Taiwan, a mountainous subtropical island with an approximate population of 24 million, is not yet fully understood. In this study, we investigate the impacts of the PJ pattern on the summer temperature and heatwave characteristics in Taiwan on the interannual timescale using long‐term station‐based temperature and rainfall dataset. We found an island‐wide increase in temperature during the positive phase of the PJ pattern, which is characterized by an anticyclonic anomalous circulation over Taiwan. Meanwhile, the averaged effective area and frequency of heatwave extremes over Taiwan have increased significantly, indicating an increase of exposure to heatwaves. Our examinations of large‐scale environment suggest that the adiabatic warming due to subsidence anomaly associated with the anticyclone over Taiwan is primary contributor of surface warming, which is balanced by diabatic cooling and meridional advective cooling on a seasonal timescale. Our study consolidated the links between the PJ pattern as a climate driver, hot summers and increased summer heatwave events over Taiwan. By combining with the seasonal prediction systems and early warning systems, such understanding can help sectors that are vulnerable to heat stress to prepare for potential hazards.

How much of Typhoon Morakot's extreme rainfall is attributable to anthropogenic climate change? - Chung‐Chieh Wang; Li‐Shan Tseng; Chien‐Chang Huang; Shih‐How Lo; Cheng‐Ta Chen; Pi‐Yu Chuang; Nan‐Chou Su; K. Tsuboki (International Journal of Climatology, 2019)
Typhoon Morakot (2009), which made landfall in Taiwan during August 7–9, 2009, produced the highest rainfall and became the deadliest typhoon ever recorded in Taiwan since 1958. To assess the role of anthropogenic climate change in the typhoon‐related torrent, we compare the water budget between a pair of cloud‐resolving sensitivity experiments. The pair consists of a control simulation that reproduces Typhoon Morakot (2009) in current climate and a sensitivity simulation in which the same storm is placed in a slightly different climate background where the late 20th century anthropogenic climate change signal is removed. The anthropogenic signal is estimated with the CMIP5 experiments of 18 models for the period of 1985–2005, during which the global warming trend is discernible. In climate states that differ merely by a 20‐year mean anthropogenic change, Morakot (2009) yields 3.4–3.6% more total rainfall in the control experiment than its sensitivity counterpart within a radius of 300–500 km from the storm centre. Water budget analysis indicates that the increase in typhoon rainfall is mainly resulted from the enhanced convergence of vapour flux. The enhancement is, in turn, contributed by the increased tropospheric moisture due to global warming and, to a lesser extent, by a more active secondary circulation in the storm that is associated with the anthropogenic climate change.